ISOLASI DAN SELEKSI BAKTERI ASAM LAKTAT DARI YOGHURT PRODUKSI INDUSTRI RUMAH TANGGA DI PEKANBARU YANG BERSIFAT ANTIBAKTERI TERHADAP Escherichia coli DAN Salmonella typhi - Lili Yani; Rodesia Mustika Roza; Atria Martina (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The occurance of Lactic Acid Bacteria (LAB) in yoghurt produced by home industry inPekanbaru as probiotic potentially improve intestinal physiological function, useful forhealth as well as prevention of the growth of pathogenic bacteria. The purposes of thisstudy were to calculate the total LAB population of yoghurt with the effect of mango andstrawberry juice during different storage process, and also to determine the ability ofantibacterial activity against Escherichia coli and Salmonella typhi. The population of LABin yoghurt was 4,0 × 10 7 – 2,9 × 10 8 CFU/ml. Antimicrobial activity assay used the welldiffusion method. The mango juice yoghurt incubated in 7 day was the most effective forEscherichia coli with the inhibition zone 27,1 mm. While the mango juice yoghurtincubated in 3 day was the most effective for Salmonella typhi with inhibition zone 29,9mm.